PELATIHAN MEDIA LEAFLET SECARA HYBRID DAPATi MENINGKATKAN i PENGETAHUAN PENCEGAHAN KOMPLIKASI DIABETIKi DI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - MARBUN, VIKTOR EDYWARD; sembiring, Johannes; syafitri, anggun (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Diabetes mellitusi (DM) is a chronic disease that can be caused by genetic factors, lack of insulin production by the pancreas, or because the insulin produced does not work optimally. DM can cause various complications, such as disorders of the heart and blood vessels, nervous system, kidneys, and increase the risk of infection. Most DM sufferers already have a fairly good level of knowledge. This activity aims to increase understanding regarding the prevention of diabetes complications in Type 2 DM sufferers in the Tanjung Morawa Health Center work area. Education was provided using leaflet media through a hybrid method, namely directly (offline) and online, to 63 people with Type 2 DM at the Tanjung Morawa Health Center. Before being given education through leaflets and e-leaflets, most respondents had a level of knowledge in the moderate category, namely 28 peoplei (44.44%). After being given educationii, well-knowni majority is 48 people (76.19%). p = 0.000, which means that there is a significanti difference in the level iof knowledgei of the DM in the Tanjung Morawa regency